The Glowport – Illuminated vitrectomy trocar cannulas - Prithvi Chandrakanth; Shishir Verghese; KS Chandrakanth; Priya Basaiawmoit; Verghese Joseph (Indian Journal of Ophthalmology)
The use of small-gauge trocar cannulas during transconjunctival sutureless pars plana vitrectomy (PPV) facilitates the smooth transition of instruments into the posterior segment and reduces trauma. However, room lighting is routinely dimmed during PPV, thereby making cannula visualization difficult and hence compromising efficient instrument exchange. We report the use of a frugal, fluorescent “glow-in-the-dark” ring placed over vitrectomy cannulas to visualize the cannula entry, thereby providing a smooth and efficient instrument exchange. We 3D-printed phosphorescent rings of optimum inner diameter to comfortably fit around the trocar cannula (The Glowport). Two such rings are fitted into the two trocar cannulas prior to surgery initiation. The cannulas are then passed via sclerostomy as performed in routine PPV. The light from the fiberoptic endo-illuminator is focused over the rings for approximately 5 seconds to activate the photoluminescence. Under mesopic conditions, the fluorescence provides visualization of the cannula entry and helps in the facilitation of smooth entry and exchange of instruments into the globe for performing vitreoretinal surgical procedures, which helps in reducing ocular touch errors as well as surgical time. The Glowport is a frugal device retrofitted onto the trocar cannulas and helps in the smooth entry and exchange of instruments under darkroom conditions, which are required in vitreoretinal surgery.